1976
DOI: 10.1037/0022-0167.23.3.259
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of helping skills training: Effects on helpers' verbal responses.

Abstract: The present and future utilization of paraprofessional manpower necessitates systematic training of such workers for their human service roles. The impact of a training program designed by Danish and Hauer for basic helping skills was evaluated. In particular, changes in the verbal responses used by human service workers in training were investigated. Using a rating system based on the training program's goals, helpers' responses in simulated helping interviews were categorized. Responses which summarized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…In a recent study (Danish, D'Augelli & Brock 1976) trainees were found to use significantly more content responses and affective responses after completing the Danish and Hauer (1973) program. Significant decreases in the use of influence, advice, and closed questions were also found.…”
Section: Hypothesesmentioning
confidence: 97%
“…In a recent study (Danish, D'Augelli & Brock 1976) trainees were found to use significantly more content responses and affective responses after completing the Danish and Hauer (1973) program. Significant decreases in the use of influence, advice, and closed questions were also found.…”
Section: Hypothesesmentioning
confidence: 97%
“…Simultaneously, decreases in leading or directive responses, such as advice and questions, and a decrease in self-oriented responses were expected. The training has been effective in producing such results in the past (e.g., Danish, D'Augelli, & Brock, 1976;D'Augelli & Levy, 1978).…”
Section: Trainingmentioning
confidence: 99%
“…Training programs to enhance helping skills have been developed for college students, professionals, medical students, and hospital person-325 1982, 155 [325][326][327][328][329][330][331][332][333][334] NUMBER 3 (FALL 1982) nel (Carkhuff, 1969;Carkhuff & Truax, 1965a, 1965b; Danish, D'Augelli, & Brock, 1976;Danish & Hauer, 1973;Ginsberg & Danish, 1979;Ivey, 1971; Moreland, Ivey, & Phillips, 1973). Although little is known about maximizing the qualities of low-income helpers, the counseling literature suggests the importance of such helping skills as communication skills and problem-solving skills.…”
mentioning
confidence: 99%
“…Training programs to enhance helping skills have been developed for college students, professionals, medical students, and hospital person-325 1982, 155 325-334 NUMBER 3 (FALL 1982) nel (Carkhuff, 1969;Carkhuff & Truax, 1965a, 1965b; Danish, D'Augelli, & Brock, 1976;Danish & Hauer, 1973;Ginsberg & Danish, 1979;Ivey, 1971;Moreland, Ivey, & Phillips, 1973 (Carkhuff, 1969;Ivey, 1971), and other verbal behaviors (e.g., question asking, summarization statements) may allow the counselor to obtain information from the client (Danish & Hauer, 1973;Ivey, 1971). A problem-solving format may aid in the analysis of problems and alternative solutions (Goldfried & Davison, 1976).…”
mentioning
confidence: 99%